Pensare la sovranità alimentare nell’Europa d’Oltremare: Aruba, Saint-Pierre e Miquelon, Belep (Nuova Caledonia) - Lara Giordana (Archivio Antropologico Mediterraneo)
The “archipelago” of “Overseas Europe” spans three oceans and has about six million inhabitants. It is characterized by a great variety of territories, societies and cultures, languages ​​and ecosystems, climates, and statutes. This contribution aims to investigate how some small islands that are Overseas Countries and Territories (OCT) of the European Union, or are part of them, formulate food sovereignty and food justice; and how, not being politically independent but endowed with individual forms of autonomy, they restore a complex and plural image of food sovereignty. We will explore the ways in which three different and distant societies of the European archipelago navigate the interwining of colonialism and autonomy, rights of access to land and sea, insularity and isolation, mobility and regional relations, to trace their own forms of food sovereignty: Aruba (NL), Saint-Pierre and Miquelon (FR) and the Belep Islands (Kanaky New Caledonia - FR).